SEHATI PROGRAMME: Building the capacity of local government to implement, sustain and scale up STBM and sanitation marketing in Indonesia - Angelina Yusridar; Susanne Shatanawi; Catur Adi Nugroho (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Despite the Ministry of Health’s National Sanitation Strategy (STBM) initiated in 2008 to reduce the spread of diarrheal diseases, Indonesia still suffers from open defecation, as the dominant part of the rural population does not have access to improved sanitation services with only 57% As a consequence of too much focus on meeting the MDG sanitation targets, most government programmes tend to concentrate on construction of new infrastructure (STBM pillar 1: stop open defecation). In addition to this, more priority seems to have been given to the quantity of facilities rather than their quality in the long run. The result is infrastructure that deteriorates to a level that can no longer provide access to safe sanitation facilities to those who are normally using the facilities. Therefore, in 2016, Sustainable Sanitation and Hygiene Programme for Eastern Indonesia (SEHATI) was designed, in a consortium reuniting Simavi and 5 local partners. The overall goal of SEHATI is to achieve district wide – access to, and utilisation of, sustainable and improved sanitation and hygiene facilities, and to contribute towards the government’s target of providing universal access to WASH for all by 2019. SEHATI aims to strengthen the capacity of the local authorities at district, sub-district and village level to implement a sustainable STBM 5 pillars in the community in order to achieve the national goal of universal access in2019. The programme supports the central and local governments on sustaining and scaling up STBM 5 pillars by creating an enabling environment. SEHATI works with national and local authorities as well as private sectors in 7 districts in Eastern Indonesia. To achieve the goal, Simavi works together with 5 local NGOs to implement the programme. The local partners are the catalyst for change by building the capacities and systems of the district government responsible for STBM implementation. District governments are equipped to take the lead in planning, budgeting and monitoring STBM interventions. Subsequently, the district team increases the capability of sub-district government and Primary Health Care to plan, budget, promote and monitor STBM 5 pillars at village level. After that, the district and sub-district team assist the village government in planning, budgeting and implementing STBM 5 pillars in the communities. When the capacities are enhanced, local actors are more likely to replicate and scale up the STBM throughout the districts. Seven intervened districts are able to issue STBM 5 pillars related regulation to ensure that the programme is implemented properly in their area. District governments have capacity to oversee the plan and budget for STBM during planning processes. In addition, STBM team has been established at district, sub-district and village level to execute the programme thoroughly. As a result, at the end of 2017, more than 500.000 people at intervened villages have knowledge on STBM 5 pillars13 out of 210 intervened villages have been declared 100% STBM. Although SEHATI works at government level to sustain the implementation of 5 pillars of STBM, measuring the impact of this programme may take several years. Staff rotation and political issues at district and village level often hamper the process of the programme. Similarly, government bodies have their own priorities programme so to some extent STBM has lack of attention. Therefore, to realize the ambitious goal of achieving universal access in 2019, it is necessary advocate for STBM 5 pillars practises at national (POKJA AMPL) and district level (i.e. head of districts). SEHATI PROGRAMME: Building the capacity of local government to implement, sustain and scale up STBM and sanitation marketing in Indonesia